2007
DOI: 10.1152/ajpheart.01393.2006
|View full text |Cite
|
Sign up to set email alerts
|

Rho kinase activation plays a major role as a mediator of irreversible injury in reperfused myocardium

Abstract: Hamid SA, Bower HS, Baxter GF. Rho kinase activation plays a major role as a mediator of irreversible injury in reperfused myocardium. Am J Physiol Heart Circ Physiol 292: H2598 -H2606, 2007. First published January 12, 2007; doi:10.1152/ajpheart.01393.2006.-Intracellular signal transduction events in reperfusion following ischemia influence myocardial infarct development. Here we investigate the role of Rho kinase (ROCK) activation as a specific injury signal during reperfusion via attenuation of the reperfus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
117
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(119 citation statements)
references
References 36 publications
2
117
0
Order By: Relevance
“…It has been recognized that low amounts of NO generated by constitutive NOS (eNOS and nNOS) are beneficial (18). There have also been some reports that eNOS overexpression reduces I/R and hypoxic injury in a variety of tissues and cells (19)(20)(21)(22). Therefore, we determined the role of eNOS in the involvement of the eNOS protein in LPS-induced kidney tolerance.…”
Section: Discussionmentioning
confidence: 94%
“…It has been recognized that low amounts of NO generated by constitutive NOS (eNOS and nNOS) are beneficial (18). There have also been some reports that eNOS overexpression reduces I/R and hypoxic injury in a variety of tissues and cells (19)(20)(21)(22). Therefore, we determined the role of eNOS in the involvement of the eNOS protein in LPS-induced kidney tolerance.…”
Section: Discussionmentioning
confidence: 94%
“…In the present study, we showed that fasudil administered just after reperfusion but not 30 min after reperfusion protected the stunned myocardium. Hamid et al reported that Rho-kinase activity increased 10 min after reperfusion but not during ischemia, and that Y27632 administered during early reperfusion significantly reduced the infarct size [8]. Thus fasudil administration during early reperfusion may protect against myocardial stunning as well as myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
“…Preischemic administration of the Rho-kinase inhibitors fasudil and Y-27632 decreased the incidence of arrhythmias and myocardial infarct size in rats subjected to transient LAD occlusion [5,6]. Recently, administration of the Rho-kinase inhibitor Y-27632 at early reperfusion was reported to have a cardioprotective effect against myocardial infarction [7,8]. Shibata et al 6 paragraph 3 deleted.…”
Section: Introductionmentioning
confidence: 99%
“…In regard to this, it has recently been shown that ROCK) and their associated signaling pathways play pivotal roles in the development of (experimental) IRI. ROCK-inhibitors such as fasudil or Y-27632 have been shown to provide beneficial effects concerning different ischemic events such as renal (Kentrup D. et al 10 A.D.; Kentrup D. et al 2010;Prakash et al 2008;Teraishi et al 2004;Versteilen et al 2006;Versteilen et al 2011) myocardial (Bao et al 2004Hamid, Bower & Baxter, 2007;Wolfrum et al 2004), cerebral (Satoh et al 2008;Toshima et al 2000), hepatic (Du & Hannon, 2004;Ikeda et al 2003;Takeda et al 2003), and gastrointestinal (Santen et al 2010) ischemia. However, the exact mechanisms involved remain to be fully elucidated.…”
Section: Rock Inhibition In Ischemia Reperfusion Injurymentioning
confidence: 99%